2010
DOI: 10.1530/rep-10-0200
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of sox9 duplicates in catfish: localization, differential expression pattern during gonadal development and recrudescence, and hCG-induced up-regulation of sox9 in testicular slices

Abstract: In vertebrates, sox9 is a transcription factor that plays a crucial role in testicular development and chondrogenesis. Here, we report cloning of isoforms of sox9 (sox9a and sox9b) from air-breathing catfish Clarias gariepinus, which undergoes an annual reproductive cycle. Tissue distribution pattern showed differential expression of sox9 duplicates, wherein both forms were highly expressed in brain and gonads. Furthermore, we observed a dimorphic expression pattern of sox9a and sox9b in both adult and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…These results suggest that SOX24 plays a role as a transcriptional regulator during oogenesis [35]. Our results regarding the change of mRNA in PV compared to VT and FOM as was found in blue gourami are in agreement with the result for SOX9 transcription in oogensis in catfish [34].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results suggest that SOX24 plays a role as a transcriptional regulator during oogenesis [35]. Our results regarding the change of mRNA in PV compared to VT and FOM as was found in blue gourami are in agreement with the result for SOX9 transcription in oogensis in catfish [34].…”
Section: Discussionsupporting
confidence: 91%
“…A high level of sperm was found in the testis in both these stages [32], and spermatogenesis was controlled by gonadotropins (FSH and LH) and androgens hormones [20] [33]. Raghuveer and Senthilkumaran [34] observed that in breathing catfish Clarias gariepinus, which underwent an annual reproductive cycle, a dimorphic expression pattern of SOX9a and SOX9b was found in both adult and developing gonads using RT-PCR, indicating that SOX9a retained its function in testis while SOX9b might play a new role in ovary, as was revealed in the current study in blue gourami using real-time PCR.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, dmrt1 expression was negligible or undetectable in female gonads during gonadal ontogeny. Previously, we isolated 2 duplicate isoforms of sox9 which were named sox9a and sox9b [Raghuveer and Senthilkumaran, 2010b]. In this study, sox9a and sox9b transcripts were first noticed at low levels in indifferent gonads at 30 dph and at moderately high levels in bipotential gonads around 40 dph ( fig.…”
Section: Histological Observation Of Gonadal Development In Catfishmentioning
confidence: 80%
“…Sections were then incubated overnight at 4 ° C either with Dmrt1, Sox9, Cyp19a1, or Foxl2 antibodies. The specificity of Dmrt1 [Raghuveer and Senthilkumaran, 2009], Sox9 [Raghuveer and Senthilkumaran, 2010b] and Foxl2 [Sridevi and Senthilkumaran, unpublished data] antibodies used for IHC were evaluated previously in our laboratory. In brief, we used catfish-specific antibodies that were raised in our laboratory for the localization of Dmrt1 and Foxl2 proteins.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation